Effects of altitude on the energetics of human best performances in 100 m running: a theoretical analysis - Arsac, L. M. (European Journal of Applied Physiology, 2002)
The present study was designed to investigate the role of reduced air density on the energetics of 100 m running at altitude. A mathematical supply-demand model was used where supply had two components, aerobic and anaerobic and demand had three components: the cost of overcoming non-aerodynamic forces (Cna), the cost of overcoming air resistance (Caero), and the cost due to changes in the runner's kinetic energy (Ckin). Actual instantaneous-speed curves recorded in 100 m world champions were modelled at sea level. Then I calculated improvements in 100 m running times and changes in the components of the energy cost with changes in altitude from 0 m to 4,000 m. For the 100 m world championship for men, the model predicted times of 9.88 s at sea level, 9.80 s at 1,000 m, 9.73 s at 2,000 m, 9.64 s at 4,000 m and 9.15 s in the hypothetical situation where the air resistance was nil. In the counterpart for women the corresponding times were 10.85 s, 10.76 s, 10.70 s, 10.60 s and 10.04 s. The Caero was 12%-13% of demand at sea level, 10%-11% at 2,000 m and 8%-9% at 4,000 m. When Caero decreased this led to better performance by making more energy available for acceleration. Accordingly, Ckin increased from 20%-24% at sea level to 23%-27% at 4,000 m. There was no effect of altitude specific to body size.